Inwardly Rectifying Potassium Channel Kir2.1 and its “Kir-ious” Regulation by Protein Trafficking and Roles in Development and Disease - Hager, Natalie A.; McAtee, Ceara K.; Lesko, Mitchell A.; O’Donnell, Allyson F. (Frontiers in Cell and Developmental Biology, 2022)
Potassium (K+) homeostasis is tightly regulated for optimal cell and organismal health. Failure to control potassium balance results in disease, including cardiac arrythmias and developmental disorders. A family of inwardly rectifying potassium (Kir) channels help cells maintain K+ levels. Encoded by KCNJ genes, Kir channels are comprised of a tetramer of Kir subunits, each of which contain two-transmembrane domains. The assembled Kir channel generates an ion selectivity filter for K+ at the monomer interface, which allows for K+ transit. Kir channels are found in many cell types and influence K+ homeostasis across the organism, impacting muscle, nerve and immune function. Kir2.1 is one of the best studied family members with well-defined roles in regulating heart rhythm, muscle contraction and bone development. Due to their expansive roles, it is not surprising that Kir mutations lead to disease, including cardiomyopathies, neurological and metabolic disorders. Kir malfunction is linked to developmental defects, including underdeveloped skeletal systems and cerebellar abnormalities. Mutations in Kir2.1 cause the periodic paralysis, cardiac arrythmia, and developmental deficits associated with Andersen-Tawil Syndrome. Here we review the roles of Kir family member Kir2.1 in maintaining K+ balance with a specific focus on our understanding of Kir2.1 channel trafficking and emerging roles in development and disease. We provide a synopsis of the vital work focused on understanding the trafficking of Kir2.1 and its role in development.